Milk : the fight for purity - Giblin, James (New York : Crowell, 1986)
Traces the history of the centuries-long effort of philanthropists, scientists, and consumers to make milk a reliably pure and safe product.
Includes index.
Bibliography: p. 100-102.
Keywords: Milk hygiene -- History -- Juvenile literature; Milk as food -- History -- Juvenile literature; Dairying -- History -- Juvenile literature; Milk hygiene -- United States -- History -- Juvenile literature; Milk as food -- United States -- History -- Juvenile literature; Dairying -- United States -- History -- Juvenile literature; Milk; Milk hygiene; Dairying